Catalytic cycloaddition of acrylates to norbornadiene. Kinetics and mechanism - I. E. Efros; O. A. Nikityuk; D. V. Dmitriev; V. R. Flid (Тонкие химические технологии)
Kinetics of [2+2+2]-cycloaddition of acrylates to norbornadiene in the presence of η3-bis(allyl) nickel was studied. The thermodynamic parameters were determined. Kinetics equations for all of the isomer reaction products were found. The data obtained agree with the formerly proposed mechanism.